w-6=-9

Simple and best practice solution for w-6=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w-6=-9 equation:


Simplifying
w + -6 = -9

Reorder the terms:
-6 + w = -9

Solving
-6 + w = -9

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + w = -9 + 6

Combine like terms: -6 + 6 = 0
0 + w = -9 + 6
w = -9 + 6

Combine like terms: -9 + 6 = -3
w = -3

Simplifying
w = -3

See similar equations:

| (8x+3)2=27 | | 1/2x^2-1/14-3/7=0 | | 2q+6=5 | | -5+u=-2 | | 0.16x+0.9(x-4)=0.01(2x-2) | | -y^2=-2y^2-6 | | 2x-11x=36 | | I=(2000)(3.7)(3.5) | | 1/12-9/16 | | x/4+1.2=-5.2 | | 12-3(2w+1)=10w-3(10+w) | | 7x/10+2=5x/6 | | 9w+2/2=2w+8/3+6 | | 5/X-2=4/7 | | y=1/5x+5 | | 3/8-5/18 | | 12r^2-17r-5=0 | | 7x-2/3=-5/3x-1/4 | | 4x+5(600-x)=2680 | | 5z-6=34 | | 4s^2-11s=3 | | 1/3w-3/5=-1/4 | | 20x^2+28x-3=0 | | 10x-8x+4=3x-16 | | 4(3n+3)=6(9n+7)+7 | | 4z-6=34 | | 3t^2+4t=15 | | 5t-8=38-t | | 7u+17-12u=-38 | | y=-9/8x | | u/6+13.1=-6.1 | | 4x+5(600-x)=2800 |

Equations solver categories